The comparative analysis of Global Youth Tobacco Survey 2003, 2008, 2014 in the Kyrgyz Republic - Chinara Bekbasarova (Tobacco Induced Diseases, 2018)
Background The GYTS, a component of the Global Tobacco Surveillance System, is a global standard for systematically monitoring youth tobacco use (smoking and smokeless) and tracking key tobacco control indicators. GYTS is a nationally representative school-based survey among students aged 13 to 15 years. GYTS-Kyrgyzstan was conducted in 2003, 2008 and 2014 by support WHO and CDC USA.